Evaluation of Susceptibility to Shallow Landslides Based on the Application of Bivared Statistics: Preliminary Results - Dias, Helen Cristina; Bateira, Carlos Valdir de Meneses; Pissato, Edilson; Martins, Tiago D.; Vieira, Bianca Carvalho (Revista do Departamento de Geografia, 2018)
The aim of this paper was to define the shallow landslides susceptibility on Caraguatatuba county, based on statistical analysis of morphological parameters. The production of morphological maps of curvature, aspect, hypsometry and slope were based on SRTM 30 m. From this, it was made an bivariate statistical analysis based on informative value. Such index it is responsible to relate morphological classes and shallow landslides from past events. The results showed that certain morphological classes tend to be more susceptible to occurrence of the process. So, that a success rate of 78% of the final susceptibility map was obtained. Thus, it was possible verify preliminary preferred classes to landslide occurrence in the area, such result demonstrate the importance of future studies about landslides and incorporation of other conditioning factors, such for example geology.